Java : The complete reference - Schildt, Herbert (New York : McGraw-Hill Education, 2018)
"Fully updated for Java SE 9, Java: The Complete Reference, Tenth Edition explains how to develop, compile, debug, and run Java programs. Bestselling programming author Herb Schildt covers the entire Java language, including its syntax, keywords, and fundamental programming principles. You'll also find information on key portions of the Java API library, such as I/O, the Collections Framework, the stream library, and the concurrency utilities. Swing, JavaFX, JavaBeans, and servlets are examined and numerous examples demonstrate Java in action. Of course, the new module system added by Java SE 9 is discussed in detail. This Oracle Press resource also offers an introduction to JShell, Java's new interactive programming tool"--
Includes index.
CSE
Keywords: Java (Computer program language); Computer science; Internet programming; COMPUTERS / Programming Languages / Java